New Straits Times 3 Januari 2007 (The New Straits Times Press (M) Bhd, 2007)
The formation of Malaysia was followed by confrontatinwith Indonesia and the ejection of Singapore. These were hectic times for Tun Dr Ismail Abdul Rahman, and the toll on his worsening health led to his resignation